2018
DOI: 10.1097/sla.0000000000002058
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-infiltrating Neutrophils is Prognostic and Predictive for Postoperative Adjuvant Chemotherapy Benefit in Patients With Gastric Cancer

Abstract: TIN in gastric cancer was identified as an independent prognostic factor, which could be incorporated into standard TNM staging system to refine risk stratification and predict for overall survival benefit from postoperative chemotherapy in patients with gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
163
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 181 publications
(171 citation statements)
references
References 51 publications
8
163
0
Order By: Relevance
“…whereas IFN-b can regulate the antitumor phenotype of N1. 9,28,42 In our study, low TIN predict a favorable survival for biliary cancer.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…whereas IFN-b can regulate the antitumor phenotype of N1. 9,28,42 In our study, low TIN predict a favorable survival for biliary cancer.…”
Section: Discussionsupporting
confidence: 53%
“…TIN can be attracted by granulocyte colony‐stimulating factor (G‐CSF), granulocyte‐macrophage colony‐stimulating factor (GM‐CSF), chemokine (C‐X‐C motif) ligand (CXCL)1, CXCL2, CXCL5 and CXCL8 secreted by cancer cells, endothelial cells or fibroblasts . Simultaneously, G‐CSF and transforming growth factor beta (TGF‐β) can control the immunosuppressive function of N2 by regulating transcription factors inhibitor of DNA binding 1 (ID1), retinoblastoma 1 (RB1) and interferon regulatory factor 8 (IRF8), whereas IFN‐β can regulate the antitumor phenotype of N1 . In our study, low TIN predict a favorable survival for biliary cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al19 showed that TANs are an independent and unfavorable factor in the prognosis of gastric cancer patients. However, Sun et al26 found that gastric cancer patients with high CD66b + TAN levels gain a survival benefit and are prone to improved OS from postoperative adjuvant chemotherapy. In contrast, low TAN levels identified a subgroup of muscle invasive bladder cancer (MIBC) patients who appeared to benefit from adjuvant chemotherapy 16.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have revealed that tumor‐infiltrating neutrophils are associated with a better prognosis in CRC and might promote antitumor immunity 22, 25. CD66b was found to be a reliable marker to identify TANs in cancer tissues using immunohistochemistry, including in CRC tissues 17, 19, 22, 24, 26. Thus, the prognostic role of TANs in CRC is not yet conclusive, and the relationship of IL‐37 and CD66b + TANs has not been previously elucidated.…”
Section: Introductionmentioning
confidence: 96%
“…Formalin-fixed paraffin-embedded surgical specimens were used for tissue microarray (TMA) construction and subsequent immunohistochemistry study as described previously. 20 The TMA slide was dried 2 hr at 608C, the sections were dewaxed in xylene and graded alcohols, hydrated and washed in phosphate-buffered saline. After the endogenous peroxidase was inhibited by 3% H 2 O 2 for 30 min, the sections were pretreated in a microwave oven (15 min in sodium citrate buffer, pH 6) and then incubated with 10% normal goat serum for 60 min.…”
Section: Immunohistochemistrymentioning
confidence: 99%